Motivasi, Pengajaran dan Pembelajaran - Zakiah Nur Harahap; Nurul Azmi; Wariono Wariono; Fauziah Nasution (Journal on Education, 2023)
Motivation is seen from the meaning of the word, motivation (motivation) means things that give rise to encouragement or circumstances that give rise to encouragement. Motivation can also be said to be energy to generate drive within oneself (drive arousal). There are three main components in motivation, namely: needs, drives and goals. Judging from the KBBI teaching is defined as a process, deed, method of teaching or teaching, teaching matters, everything about teaching, about experiences, events experienced or seen. On a macro level, learning is a process that is pursued so that students can optimize their potential, both cognitive and socio-emotional, effectively and efficiently to achieve the expected behavior change. While macro learning is related to two paths, namely the individual who learns and the arrangement of external components so that the learning process occurs in the individual who learns.